2021
DOI: 10.1002/stem.3340
|View full text |Cite
|
Sign up to set email alerts
|

Engineering-inspired approaches to study β-cell function and diabetes

Abstract: Strategies to mitigate the pathologies from diabetes range from simply administering insulin to prescribing complex drug/biologic regimens combined with lifestyle changes. There is a substantial effort to better understand β-cell physiology during diabetes pathogenesis as a means to develop improved therapies. The convergence of multiple fields ranging from developmental biology to microfluidic engineering has led to the development of new experimental systems to better study complex aspects of diabetes and β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…51,52 In general, multi-step fabrication methods have limited ease of use and reproducibility of microfluidic devices and prevented their widespread adoption and use by laboratories. 20,53,54 In this study, we sought to address the above-mentioned limitations by designing a novel 3D culture platform that recreates components of the in vivo microenvironment, namely physiologically relevant mass transport conditions and islet-ECM mechanochemical signaling. Previously, we have shown that islet encapsulation within fibrillar scaffolds prepared with polymerizable type I oligomeric collagen supports maintenance of islet morphology, viability, and function beyond 14 days in vitro in static culture conditions.…”
Section: Lab On a Chip Papermentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 In general, multi-step fabrication methods have limited ease of use and reproducibility of microfluidic devices and prevented their widespread adoption and use by laboratories. 20,53,54 In this study, we sought to address the above-mentioned limitations by designing a novel 3D culture platform that recreates components of the in vivo microenvironment, namely physiologically relevant mass transport conditions and islet-ECM mechanochemical signaling. Previously, we have shown that islet encapsulation within fibrillar scaffolds prepared with polymerizable type I oligomeric collagen supports maintenance of islet morphology, viability, and function beyond 14 days in vitro in static culture conditions.…”
Section: Lab On a Chip Papermentioning
confidence: 99%
“…51,52 In general, multi-step fabrication methods have limited ease of use and reproducibility of microfluidic devices and prevented their widespread adoption and use by laboratories. 20,53,54…”
Section: Introductionmentioning
confidence: 99%
“…Numerous stem cell therapy companies are attempting to engineer pancreatic tissues [149]. The pancreas is an organ of both the endocrine and exocrine systems, typically known for its role in controlling blood glucose levels.…”
Section: D Bioprinting Using Ecm-based Bioinksmentioning
confidence: 99%